From Family Law to Financial Disputes: Expanding the Role of Indonesia’s Religious Courts in the Sharia Economy - Samson, Nur Aida Tahirulla; Warits, Abd (Santara: Journal of Islamic Law and Humanity, 2025)
The rapid development of Islamic finance in Indonesia has generated a growing number of disputes requiring legal resolution based on sharia principles. Historically, such cases fell under the jurisdiction of general courts, creating uncertainty for Muslim litigants. The enactment of Law No. 3/2006 fundamentally redefined the authority of Religious Courts by granting them exclusive jurisdiction over sharia economic disputes, including those related to Islamic banking, insurance, and financial contracts. This study aims to analyze how this authority is exercised in practice, with a specific focus on the Religious Court of Sumenep as a case study. Using a socio-legal and qualitative approach, the research draws on primary data from court decisions and interviews, complemented by secondary legal sources. The findings demonstrate that the Religious Court of Sumenep has effectively applied its expanded mandate, resolving disputes with greater accessibility and cultural legitimacy for Muslim litigants. However, challenges remain, particularly in judicial capacity and technical expertise in complex financial transactions. The study contributes to the discourse on judicial reform in Muslim-majority contexts, highlighting the need for continuous capacity building and institutional support to strengthen the role of Religious Courts in promoting legal certainty and advancing the Islamic economy in Indonesia